Environmental Accounting Adoption and Disclosure: Zimbabwe Stock Exchange Listed Companies: Array - Dzomira, Shewangu; Ndlovu, Ivonne (The Journal of Accounting and Management, 2020)
The concern for the environment and environmental accounting is becoming increasingly important around the world. Thus the concept of environmental accounting urges corporations to be more accountable and transparent on the impact made on the environment. The main purpose of the study was to ascertain the level of adoption and disclosure of environmental information among companies listed on the Zimbabwe Stock Exchange. Twenty companies from the high and medium environmental impact sectors were sampled from the sixty five companies listed on the Zimbabwe Stock Exchange using purposive sampling technique. Qualitative content analysis through QDA Miner software analytical tool was used to analyze the secondary data in the form of annual reports. The themes that were used to analyze environmental disclosure are environmental policy, environmental impact, environmental infrastructure, strategic goals and environmental policy implementation. The findings show that companies in medium impact sectors are disposed to disclose environmental information as much as the companies in the high impact sector although that is contradictory to the legitimacy theory. Thus the study recommends that companies listed on the Zimbabwe Stock exchange adopt and disclose environmental information in their annual reports.